Valuation of Bankrupt Firms - Gilson, Stuart C.; Hotchkiss, Edith S.; Ruback, Richard S. (Review of Financial Studies, 2000)
This study compares the market value of firms that reorganize in bankruptcy with estimates of value based on management's published cash flow projections. We estimate firm values using models that have been shown in other contexts to generate relatively precise estimates of value. We find that these methods generally yield unbiased estimates of value, but the dispersion of valuation errors is very wide - the sample ratio of estimated value to market value varies from less than 20% to greater than 250%. Cross-sectional analysis indicates that the variation in these errors is related to empirical proxies for claimholders' incentives to overstate or understate the firm's value.